Review of scapular movement disorders among office workers having ergonomic risk - Depreli, O.; Angin, E. (Ios Press, 2018)
BACKGROUND: Work-related musculoskeletal disorders are the most common health problems which affect millions of office workers. OBJECTIVE: The objective of this study is to determine scapular positioning at rest and different anatomical planes, the assessment of pain, postural changes and the functionality of upper extremity that is caused by the lack of ergonomic principles among office workers of civil servants in TRNC (Turkish Republic of Northern Cyprus). METHODS: 183 individuals participated in the study and 2 groups were created by grand scores of Rapid Upper Limb Assessment (RULA) tool. Scapular dyskinesis, pain of upper extremity and back, physical functions and symptoms of upper extremity, the self-rated neck disability, cervical and upper thoracic posture of workers were assessed. RESULTS: The difference between pain situation and the results of upper extremity and neck disability scores of the participants among the groups was significant (p < 0.05). No significant difference has been found statistically among the postural angle values of individuals (p > 0.05). A significant statistical difference has been found among the groups when the results of Lateral Scapular Slide Test (LSST) is examined (p < 0.05). CONCLUSIONS: Working environment and conditions cause the wrong of working posture and thus, lead individuals to spend more energy together with physical difficulty, and consequently affect general health.
Keywords: Scapular dyskinesis; ergonomics; pain; disability; posture